Deux problèmes d’histoire des religions au monde antique: i. Le dieu sabazios et le judaïsme - Bodinger, Martin (Archaeus, 2002)
The author proposes a reconsideration of the complex discussion regarding the figure of the God Sabazios, taking into debate the questions of the origin, the attributes, the name, the iconographie and the cult of this pre-christian God. It is on the problem of the cult that Bodinger’s article is mainly focussed on. As concerns the origin, the author stresses upon the hypothesis of the Thrace origin, taking as principal argument the fact that Thrace is the only place where Sabazios was not associated with other divinities; moreover it is here that one finds the most important ammount of representations and inscriptions, the traces of sanctuaries devoted to this God. As concerns the name, rejecting the arguments of Vernadsky and Bonfante, Bodinger is inclined to give favour to the solution proposed by the Romanian researcher Gh. Mu]u, according to which the name "Sabazios" comes from "sap", solution sustained by the classical sources which certify that sabaos means spring like sap. As concerns the cult, Bodinger discusses the threefold problem of the association between Sabazios, on the one hand, and, on the other hand, Dionysos, Yahwe, respectively Hypsistos. In the framework of the whole article, it is the second ecquation, Sabazios=Yahwe, which receives the main attention. Bodinger rejects Cumont’s hypothesis of a syncretism between Sabazios and Yahwe, leaning on the argument that the main source Cumont had used was not Valerius Maximus’ epitomes, but a later copy of these. In this way the author brings his analysis to the principal conclusion that it is out of discussion to have ever existed, in Rome or in any other place, any community of Jews devoted to the God Sabazios.